Hubungan antara Gaya Kepemimpinan Transformasional dengan Motivasi Mengajar Guru di Sekolah Dasar - Endang Purnama Sari; Cahyani Cahyani; Darmawan Darmawan; Ayu Manjayani Damanik; Muhammad Rajab (CV. ITTC INDONESIA, 2025)
This study aims to examine the relationship between the principal's transformational leadership style and teacher teaching motivation in elementary schools. Transformational leadership is understood as a leadership model that is able to build an inspiring vision, provide individual attention, encourage critical thinking, and be a moral role model for teachers. Teachers who work under this kind of leadership tend to have higher motivation, strong work commitment, and satisfaction in carrying out their professional duties. The research method used is a literature study, by reviewing various scientific journals, academic books, and relevant research reports in the last 10 years. The results of the synthesis show that all dimensions of transformational leadership contribute to increasing teacher motivation in designing learning, improving competence, and creating an effective classroom atmosphere. The conclusion of this study confirms that transformational leadership style has an important role in forming a positive work environment and supporting teacher motivation in a sustainable manner.